2011
DOI: 10.1111/j.1468-3083.2010.03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and tolerability of green tea catechins in the treatment of external anogenital warts: a systematic review and meta‐analysis

Abstract: Efficacy of Polyphenon 15% and 10%, at least for the primary endpoint, is clearly indicated. Polyphenon E treatment exhibits very low recurrence rates and appears to have a rather favourable safety and tolerability profile. Recommendations for future studies should include evaluation of the efficacy of green tea catechins in the treatment of internal anogenital warts and direct comparison with its principal comparator, imiquimod.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
2
41
0
7
Order By: Relevance
“…[55][56][57] A meta-analysis concluded that sinecatechins is a safe and effective treatment, but follow-up studies are needed to determine the long-term recurrence rates. 58 Although sinecatechins may have higher clearance rates than other patient-applied therapies, this treatment does require frequent application over a longer period of time. The use of sinecatechins has not been reported in children.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…[55][56][57] A meta-analysis concluded that sinecatechins is a safe and effective treatment, but follow-up studies are needed to determine the long-term recurrence rates. 58 Although sinecatechins may have higher clearance rates than other patient-applied therapies, this treatment does require frequent application over a longer period of time. The use of sinecatechins has not been reported in children.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…In de meta-analyse van Tzellos werden in totaal 1247 patiënten geïncludeerd. 4 Hieruit blijkt dat sinecatechinszalf effectiever is dan placebo: 51% versus 36% totale genezing; relatief risico 1,42 (95%-BI 1,19 tot 1,70; p = 0,0001). De belangrijkste bijwerkingen zijn lichte, lokale huidreacties.…”
Section: Nieuwsunclassified
“…Szczyt nasilenia objawów niepożądanych występował pomiędzy 2. i 4. tygodniem leczenia, co również pokrywało się z początkiem działania leczniczego preparatu. Autorzy prac sugerują, że odczuwane objawy wiążą się z lokalną stymulacją komórek układu immunologicznego i wzrostem uwalniania cytokin prozapalnych [20][21][22][23]. Miejscowa reakcja zapalna jest prawdopodobnie wskaźnikiem skuteczności leczenia i okazuje się niezbędna do uzyskania efektu terapeutycznego.…”
Section: Metody Lecznicze Do Stosowania Samodzielnegounclassified
“…Dodatkowo odnotowano stosunkowo niski wskaźnik nawrotowości zmian w porównaniu z innymi metodami leczniczymi. Być może preparat sinekatechiny działa również na subkliniczne zmiany spowodowane zakażeniem HPV [23]. Obserwowano bardzo dobrą współpracę pacjentów podczas leczenia, co może być związane z dobrą tolerancją terapii i niskim wskaźnikiem występowania poważnych działań niepożądanych.…”
Section: Metody Lecznicze Do Stosowania Samodzielnegounclassified